Hubungan Antara Self-efficacy dan Dukungan Sosial dengan Psychological Distress pada Perawat di Rumah Sakit “X” Bandung - Maria Yuni Megarini; Trisa Genia; Yuspendi Yuspendi (Humanitas (Jurnal Psikologi), 2022)
Nurses during the Corona Virus Disease-19 (Covid-19) pandemic are expected to be able to provide professional nursing services even with the risk of contracting and even becoming victims of Covid-19. Working in a hospital with current pandemic conditions causes nurses to experience psychological disorders such as depression, anxiety and stress. The purpose of this study was to determine the relationship between self-efficacy and social support with psychological distress in nurses at "X" Hospital Bandung. The research was conducted using quantitative method with multiple regression analysis and the respondents involved were 233 nurses, both in the inpatient and outpatient departments. Data for psychological distress were obtained using the Depression Anxiety Stress Scales (DASS 42) from Lovibond, S.H. & Lovibond, P.F. (1995), self-efficacy with the Generalized Self-efficacy scale (Schwarzer & Jerusalem, 1995) and social support using The Social Provision Scale (Cutrona & Russel, 1987). The results of the study show that the value of F = 6.403 with sig = 0.002. There is a negative relationship between social support and psychological distress, and there is also a negative relationship between self-efficacy and psychological distress. Based on the results of multiple regression, it was found that the higher the social support and self-efficacy, the lower the psychological distress experienced by nurses.